PENGARUH MANAJEMEN LABA, GOOD CORPORATE GOVERNANCE , DAN RISIKO PERUSAHAAN TERHADAP TAX AVOIDANCE - Rizky Darma; Yuniarti Dwi Jayanthi Tjahjadi; Susi Dwi Mulyani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
Tax is the biggest source of income for Indonesia, so it becomes very important to improve adherence to the taxpayers in Indonesia. The fact that Indonesia has failed to achieve its target for tax income only shows that the nation still faces lack of obedience from the tax payers. Many companies in Indonesia have tried to alleviate their tax expenses, either legally (Tax Avoidance) or illegally (Tax evasion). This Research describes the effect of profit management, independent commissioners, audit committee, institutional ownership, and corporate risk may faces from practicing tax evasion legally (Tax Avoidance). In this thesis, tax avoidance is described by Abnormal Book Tax Difference, which is an abnormal form of difference tax accounting differences. Samples were taken from manufacturing companies listed in Indonesia Stock Exchange within the period of 2011 – 2015 with purposive sampling method so the result is 68 samples company will be taken. The results of this study indicate that profit management, audit committees, and corporate risk influence the practice of tax evasion (Tax Avoidance), while the independent directors and institusional ownership do not have a significant impact on the practice of tax evasion (Tax Avoidance) in Indonesia.